Pharmacological management of chronic insomnia disorder in Singapore: Recommendations from an expert panel - Roger Ho; Chau Sian Lim; Phern Chern Tor; Cyrus Su Hui Ho; Jason Wui Chi Pang; Beng Yeong Ng (Proceedings of Singapore Healthcare)
Background Chronic insomnia disorder, a condition associated with frequent and persistent difficulty in initiating or maintaining sleep, is one of the most common reasons for patients consulting general practitioners and psychiatrists in Singapore. Objectives The landscape for managing chronic insomnia disorder is constantly changing but a clear, updated guidance for its management is lacking. Methods This guidance document provides guidance and recommendation for the diagnosis, assessment, and management of chronic insomnia disorder in Singapore based on a review of the current clinical practice guidelines and recent evidence including findings specific to Singapore. Results and Conclusion This document further summarises the properties and safety profiles of various pharmacological agents and provides guidance for their use across patient profiles. Lastly, this document provides recommendations from a panel of 5 clinicians with expertise in treating patients with sleep disorders.